Sex, Thugs And Rock 'n' Roll : Teenage Rebels in Cold-War East Germany. - Fenemore, Mark (Monographs in German history., 2013)
A fascinating and highly readable account of what it was like to be young and hip, growing up in East Germany in the 1950s and 1960s. Living on the frontline of the Cold War, young people were subject to a number of competing influences. For young men from the working class, in particular, a conflict developed between the culture they inherited from their parents and the new official culture taught in schools. Merging with street gangs, new youth cultures took shape, which challenged authority and provided an alternative vision of modernity. Taking their fashion cues, music and icons from the.